2012
DOI: 10.1038/onc.2012.440
|View full text |Cite
|
Sign up to set email alerts
|

Distinct roles for fibroblast growth factor signaling in cerebellar development and medulloblastoma

Abstract: Cerebellar granule neurons are the most abundant neurons in the brain, and a critical element of the circuitry that controls motor coordination and learning. In addition, granule neuron precursors (GNPs) are thought to represent cells of origin for medulloblastoma, the most common malignant brain tumor in children. Thus, understanding the signals that control the growth and differentiation of these cells has important implications for neurobiology and neuro-oncology. Our previous studies have shown that prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 65 publications
2
32
2
Order By: Relevance
“…However, phosphorylation of FRS2 by FGFRs activates not only the PI3K/ AKT pathway (through Grb2/Gab1 binding; Ong et al, 2001), but also the MAPK/ERK pathway (through Grb2/Shp2 binding; Hadari et al, 1998). Indeed, deletion of FGFR1 and/or FGFR2 leads to decreases in phospho-MAPK/ERK and phospho-AKT levels (Emmenegger et al, 2013;Zhao et al, 2008;Cai et al, 2013;Hoch and Soriano, 2006;Loilome et al, 2009;Kondo et al, 2007), and overexpression of FGFR2b or FGFR1 increases both phospho-AKT and phospho-ERK levels (Cha et al, 2008;Freeman et al, 2003;Acevedo et al, 2007). It is known that crosstalk can occur between the PI3K/AKT and MAPK/ERK pathways (Moelling et al, 2002), thus, possibly, the MAPK/ERK pathway is being triggered congruently.…”
Section: Discussionmentioning
confidence: 99%
“…However, phosphorylation of FRS2 by FGFRs activates not only the PI3K/ AKT pathway (through Grb2/Gab1 binding; Ong et al, 2001), but also the MAPK/ERK pathway (through Grb2/Shp2 binding; Hadari et al, 1998). Indeed, deletion of FGFR1 and/or FGFR2 leads to decreases in phospho-MAPK/ERK and phospho-AKT levels (Emmenegger et al, 2013;Zhao et al, 2008;Cai et al, 2013;Hoch and Soriano, 2006;Loilome et al, 2009;Kondo et al, 2007), and overexpression of FGFR2b or FGFR1 increases both phospho-AKT and phospho-ERK levels (Cha et al, 2008;Freeman et al, 2003;Acevedo et al, 2007). It is known that crosstalk can occur between the PI3K/AKT and MAPK/ERK pathways (Moelling et al, 2002), thus, possibly, the MAPK/ERK pathway is being triggered congruently.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that Bcl6 overexpression (Tiberi et al, 2014) or direct FGF injection reduces proliferation of medulloblastoma cells in which Shh is hyperactivated (Emmenegger et al, 2013), supporting the idea that enhancing differentiation effectively prevents medulloblastoma progression in vivo.…”
Section: Pals1 Loss Forces Cell Cycle Exit Despite Hyperactive Shh Simentioning
confidence: 76%
“…During normal cerebellar GCP development, growth factors (GF), such as bFGF, antagonize Shh-pathway activity and promote differentiation (29, 30). When SMB cells were exposed to growth factors that are common components of stem cell media (bFGF and EGF; 20 ng/mL) both PI3K-AKT and RAS-RAF-MAPK pathways were activated, Shh signaling was suppressed, and SMB cells became resistant to LDE225 (Fig.…”
Section: Resultsmentioning
confidence: 99%